Fish Detection and Classification for Automatic Sorting System with an Optimized YOLO Algorithm - Ari Kuswantori; T. Suesut; Worapong Tangsrirat; Gerhard Schleining; Navaphattra Nunak (Applied Sciences, 2023)
Automatic fish recognition using deep learning and computer or machine vision is a key part of making the fish industry more productive through automation. An automatic sorting system will help to tackle the challenges of increasing food demand and the threat of food scarcity in the future due to the continuing growth of the world population and the impact of global warming and climate change. As far as the authors know, there has been no published work so far to detect and classify moving fish for the fish culture industry, especially for automatic sorting purposes based on the fish species using deep learning and machine vision. This paper proposes an approach based on the recognition algorithm YOLOv4, optimized with a unique labeling technique. The proposed method was tested with videos of real fish running on a conveyor, which were put randomly in position and order at a speed of 505.08 m/h and could obtain an accuracy of 98.15%. This study with a simple but effective method is expected to be a guide for automatically detecting, classifying, and sorting fish.
Keywords: Water Quality Monitoring Technologies; Water Quality Monitoring and Analysis; Smart Agriculture and AI